2020
DOI: 10.5603/pjnns.a2020.0064
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of the Polish versions of the Montreal Cognitive Assessment 7.2 and the Mini-Mental State Examination as screening instruments for the detection of mild neurocognitive disorder

Abstract: Introduction. Screening tests are a key step in the diagnosis of dementia and should therefore be highly sensitive to the detection of mild neurocognitive disorders (NCD). The Mini Mental State Examination (MMSE) is the most commonly used screening method. The Montreal Cognitive Assessment (MoCA) is a newer and less well-known screening tool, which has none of the limitations of the MMSE. Aim. The aim of this study was to analyse the reliability of the Polish versions of MoCA 7.2 vs MMSE in the detection of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…A total of 55 studies ( Fujiwara et al, 2010 ; Lu et al, 2011 ; Ahmed et al, 2012 ; Larner, 2012 ; Yu et al, 2012 ; Dong et al, 2013 ; Freitas et al, 2013 ; Memória et al, 2013 ; Roalf et al, 2013 ; Cummings-Vaughn et al, 2014 ; Goldstein et al, 2014 ; Kaya et al, 2014 ; Malek-Ahmadi et al, 2014 ; Yeung et al, 2014 ; Zhou et al, 2014 ; Chu et al, 2015 ; Julayanont et al, 2015 ; Ng et al, 2015 ; Trzepacz et al, 2015 ; Mellor et al, 2016 ; O’Caoimh et al, 2016 ; Tsai et al, 2016 ; Cecato et al, 2017 ; Clarnette et al, 2017 ; Janelidze et al, 2017 ; Bartos and Fayette, 2018 ; Chiu et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Cesar et al, 2019 ; Delgado et al, 2019 ; Rossetti et al, 2019 ; Townley et al, 2019 ; Wang et al, 2019 ; Pinto et al, 2019b ; Aycicek et al, 2020 ; Bello-Lepe et al, 2020 ; Dautzenberg et al, 2020 ; Freud et al, 2020 ; Senda et al, 2020 ; Serrano et al, 2020 ; Sokołowska et al, 2020 ; Thomann et al, 2020 ; González et al, 2021 ; Hemrungrojn et al, 2021 ; Masika et al, 2021 ; Rashedi et al, 2021 ; Rodríguez-Salgado et al, 2021 ; Yan et al, 2021 ; Pan et al, 2022 ; Paterson et al, 2022 ) were included in this meta-analysis from which 40 were used in the AUC analysis and 45 were used in the analysis of mean differences. Thirty-one of the included studies were used in both the AUC and mean difference analyses.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 55 studies ( Fujiwara et al, 2010 ; Lu et al, 2011 ; Ahmed et al, 2012 ; Larner, 2012 ; Yu et al, 2012 ; Dong et al, 2013 ; Freitas et al, 2013 ; Memória et al, 2013 ; Roalf et al, 2013 ; Cummings-Vaughn et al, 2014 ; Goldstein et al, 2014 ; Kaya et al, 2014 ; Malek-Ahmadi et al, 2014 ; Yeung et al, 2014 ; Zhou et al, 2014 ; Chu et al, 2015 ; Julayanont et al, 2015 ; Ng et al, 2015 ; Trzepacz et al, 2015 ; Mellor et al, 2016 ; O’Caoimh et al, 2016 ; Tsai et al, 2016 ; Cecato et al, 2017 ; Clarnette et al, 2017 ; Janelidze et al, 2017 ; Bartos and Fayette, 2018 ; Chiu et al, 2018 ; Lee et al, 2018 ; Li et al, 2018 ; Cesar et al, 2019 ; Delgado et al, 2019 ; Rossetti et al, 2019 ; Townley et al, 2019 ; Wang et al, 2019 ; Pinto et al, 2019b ; Aycicek et al, 2020 ; Bello-Lepe et al, 2020 ; Dautzenberg et al, 2020 ; Freud et al, 2020 ; Senda et al, 2020 ; Serrano et al, 2020 ; Sokołowska et al, 2020 ; Thomann et al, 2020 ; González et al, 2021 ; Hemrungrojn et al, 2021 ; Masika et al, 2021 ; Rashedi et al, 2021 ; Rodríguez-Salgado et al, 2021 ; Yan et al, 2021 ; Pan et al, 2022 ; Paterson et al, 2022 ) were included in this meta-analysis from which 40 were used in the AUC analysis and 45 were used in the analysis of mean differences. Thirty-one of the included studies were used in both the AUC and mean difference analyses.…”
Section: Resultsmentioning
confidence: 99%
“…The Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) 15 study flow diagram is shown in Figure S1 in Appendix I. From 2683 citations, 334 were selected for full‐text screening, and 13 studies were included 9,16–27 …”
Section: Resultsmentioning
confidence: 99%
“…There are also potential limitations reported in the use of the Montreal Cognitive Assessment (MoCA) as a cognitive impairment screening tool [7], where the correspondence between individual tests and their assumed cognitive domains is not robust, reflecting at least in part a current lack of consensus as to how core cognitive constructs are defined and as to which subcomponents can be subsumed under different cognitive domains [7]. These limitations among the correlations cause the cut-off scores published in the literature to diverge, and do not allow accurate prediction of cognitive impairment [8].…”
Section: To the Editorsmentioning
confidence: 99%